A phylogenomic and comparative genomic framework for resolving the polyphyly of the genus Bacillus: Proposal for six new genera of Bacillus species, Peribacillus gen. nov., Cytobacillus gen. nov., Mesobacillus gen. nov., Neobacillus gen. nov., Metabacillus gen. nov. and Alkalihalobacillus gen. nov. Issue 1 (3rd February 2020) - Patel, Sudip; Gupta, Radhey S.
Abstract : The genus Bacillus, harbouring 293 species/subspecies, constitutes a phylogenetically incoherent group. In the absence of reliable means for grouping known Bacillus species into distinct clades, restricting the placement of new species into this genus has proven difficult. To clarify the evolutionary relationships among Bacillus species, 352 available genome sequences from the family Bacillaceae were used to perform comprehensive phylogenomic and comparative genomic analyses. Four phylogenetic trees were reconstructed based on multiple datasets of proteins including 1172 core Bacillaceae proteins, 87 proteins conserved within the phylum Firmicutes, GyrA–GyrB–RpoB–RpoC proteins, and UvrD–PolA proteins. All trees exhibited nearly identical branching of Bacillus species and consistently displayed six novel monophyletic clades encompassing 5–23 Bacillus species (denoted as the Simplex, Firmus, Jeotgali, Niacini, Fastidiosus and Alcalophilus clades), interspersed with other Bacillaceae species. Species from these clades also generally grouped together in 16S rRNA gene trees. In parallel, our comparative genomic analyses of Bacillus species led to the identification of 36 molecular markers comprising conserved signature indels in protein sequences that are specifically shared by the species from these six observed clades, thus reliably demarcating these clades based on multiple molecular synapomorphies. Based on the strong evidence from multiple lines of investigations supporting the existence of these six distinct ' Bacillus ' clades, we propose the transfer of species from these clades into six novel Bacillaceae genera viz. Peribacillus gen. nov., Cytobacillus gen. nov., Mesobacillus gen. nov., Neobacillus gen. nov., Metabacillus gen. nov. and Alkalihalobacillus gen. nov. These results represent an important step towards clarifying the phylogeny/taxonomy of the genus Bacillus .